2021
DOI: 10.1080/14787210.2021.1911647
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication Behavior with antibiotics: a national cross-sectional survey in Sri Lanka

Abstract: Background: Antibiotic self-medication is common in low-and middle-income countries. This study aimed to evaluate the Sri Lankan public's knowledge about and attitudes towards antibiotic use and self-medication, and factors associated with self-medication.Methods: A national cross-sectional, interviewer-administered, survey of a random household sample (N=1100) was conducted. Factor analysis of the attitudinal items was conducted to investigate the factors associated with antibiotics self-medication.Results: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 50 publications
2
19
1
7
Order By: Relevance
“…Self-medication is a concept in which individuals use substances to ameliorate and manage their minor illnesses. Individuals are gambling with their health in the hope that some substances help their illness and the problem is better controlled [ 6 , 7 ]. It is one of the common and favored modes reestablished by the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Self-medication is a concept in which individuals use substances to ameliorate and manage their minor illnesses. Individuals are gambling with their health in the hope that some substances help their illness and the problem is better controlled [ 6 , 7 ]. It is one of the common and favored modes reestablished by the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Self-medication with antibiotics is closely associated with inappropriate antibiotic use [11]. In a recent survey of the Sri Lankan general public, nearly all participants (98%, 974/998) reported that they had used an antibiotic in the past and half of them (50%) claimed to have taken an antibiotic at least once in the three months prior to the survey [12]. Despite the fact that antibiotics cannot treat infections caused by viruses such as common cold, acute sore throat, runny nose and flu [13][14][15][16], the majority of respondents (76%) in the Sri Lankan study had used antibiotics inappropriately for these minor infections [12].…”
Section: Introductionmentioning
confidence: 99%
“…Overall knowledge on antibiotics and resistance has been almost universally found to be not satisfactory. 10,12,13,14 Given that the majority of our study participants were undergoing or had been through university education, this situation is of concern. The older group who were self-motivated to take this questionnaire are likely to be ones who are keener about the issue, as reflected in the higher knowledge score.…”
Section: Discussionmentioning
confidence: 99%